Aile sağlığı merkezine kan tahlili yaptırmak isteğiyle başvuran hastalarda depresyon görülme sıklığı ve Beck depresyon ölçeği ile skorun ölçülmesi / Depression prevalence among patients who apply to primary health care services with the request of blood sampling and measuring the score with Beck depression inventory - ÖZKAL, GÜLVAN (My University, 2023)
Birinci basamak sağlık hizmetlerine kan tahlili yaptırmak için başvuran hastaların şikayetleri sorgulandığında halsizlik, yorgunluk gibi psikiyatrik ve fiziksel hastalıklarda ortak olarak görülebilen semptomlar ile karşılaşılmaktadır. Herhangi bir şikayeti olmayıp kronik hastalıklarının takibi için belirli aralıklarla kan tahlili yaptıran veya anemi, diyabet, hipotiroidi gibi fiziksel hastalıkların varlığının araştırılmasını isteyen hastalar da aile sağlığı merkezlerine başvurmaktadır. Aile sağlığı merkezlerine başvuruların önemli bir kısmını kan tahlili yaptırmak isteyen hastalar oluşturmaktadır. Bu hastaların şikayetlerinin depresyon ile ilişkili olabileceği veya herhangi bir şikayet belirtmeseler dahi depresyon açısından risk grubunda olabilecekleri aile hekimleri tarafından göz önüne alınırsa Beck depresyon ölçeği gibi uygulanması kolay ve hızlı bir yöntemle depresyon semptomlarının varlığı ve şiddeti araştırılabilir. Bu çalışmayla aile hekimlerine depresyon tanı ve tedavisi konusunda farkındalık kazandırılmak istenmiştir. Birinci basamaktaki hekimlerin depresyon ile ilgili bilgi ve tutumlarının geliştirilmesiyle hastaların depresyon ile ilişkili fiziksel ve psikolojik semptomları henüz depresyon tanı kriterlerini karşılayacak sayı ve şiddete ulaşmadan fark edilebilir. Hastalara fiziksel egzersiz, psikososyal desteğin arttırılması ve düzenli aile hekimi izlemleri gibi koruyucu tedbirler sunulabilir. Aile hekimleri tarafından depresyon tanısı konulması sayesinde mükerrer ikinci ve üçüncü basamak sağlık hizmeti başvuruları sırasında tedavisi geciken ve hastalığının şiddeti artan bireylerin hayat kalitesi yükseltilebilir. Bu çalışmada aile hekimlerinin depresyonla mücadelede etkin rol üstlenmesinin toplum ruh sağlığının geliştirilmesine katkısı vurgulanmak istenmiştir.
The complaints of patients, who apply to primary health care services with the request of blood sampling, consist of symptoms as fatigue and tiredness which could occur due to both physical and psychiatric health problems. The patients without any complaint also apply for blood sampling because of their chronic diseases which require routine blood sampling during follow-ups. Patients worrying about their physical health apply to family health centers by requesting blood sampling with the aim of any possible organic cause as hypothyroidism, anemia and diabetes to be investigated. A major proportion of visits to family health centers belong to patients who request blood sampling. Family physicians could perform a screening for depression by applying an easy-to-use method such as Beck Depression Inventory and thus show the existence and severity of depression symptoms if they consider that the patients' symptoms could be related to depression or patients might be in the risk group for depression regardless any symptoms. The purpose of thisstudy isto raise awareness among family physicians about depression diagnosis and treatment. Patients might be offered preventive measures as physical exercise, encouragement in psychosocial support and regular family physician follow-ups. Patients' physical and psychiatric sypmtoms could be noticed, before the number and severity of depressive symptoms fulfill the diagnostic criteria for depression, with the improvement in approaches and acknowledgement of family physicians about depression. Quality of life of people could be improved, whose treatment is delayed and depression become more severe due to time loss during repetetive visits to secondary and tertiary health care services, by family physicians diagnosing depression. In this study,it was aimed to emphasize the importance of contribution of family physicians' active role in fight against depression to improve public mental health.